2020
DOI: 10.1038/s41598-019-57327-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of histological and microRNA profiles changes in rabbit skin development

Abstract: The periodic regrowth of rabbit fur is economically important. Here, we aimed to characterise the histological traits and microRNA (miRNA) expression profiles in the skin tissue of Wan Strain Angora rabbits at different weeks after plucking. Haematoxylin-eosin staining showed that hair follicles were in the telogen phase in the first week, while they were in the anagen phase from the fourth to twentyfourth weeks. In addition, two small RNA libraries derived from skin samples of Wan Strain Angora rabbits at tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Generally, prenatal HF morphogenesis development has been divided into three main periods. The morphological characteristics of hair placode, DC, DP, etc., at different periods are nearly the same in human (Muller et al, 1991), mice (Schneider et al, 2009), sheep (Zhang et al, 2019), rabbit (Ding et al, 2020) and, based on the current study, even in pig. However, the hair type and commence time points of each HF morphogenesis development stage has been shown to vary largely, e.g., secondary HF in sheep and rabbit could make the HF morphogenesis complicated, thus making them not ideal model systems for human HF research.…”
Section: Discussionsupporting
confidence: 74%
“…Generally, prenatal HF morphogenesis development has been divided into three main periods. The morphological characteristics of hair placode, DC, DP, etc., at different periods are nearly the same in human (Muller et al, 1991), mice (Schneider et al, 2009), sheep (Zhang et al, 2019), rabbit (Ding et al, 2020) and, based on the current study, even in pig. However, the hair type and commence time points of each HF morphogenesis development stage has been shown to vary largely, e.g., secondary HF in sheep and rabbit could make the HF morphogenesis complicated, thus making them not ideal model systems for human HF research.…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies carried out on Wan Strain Angora rabbits (Ding et al . 2020) found that the hair follicles were in the short telogen phase in the first week after plucking and were in anagen phase from the fourth to twenty‐fourth weeks. The long anagen phase of the hair cycle promoted the continuous growth of Wan Strain Angora rabbit hair.…”
Section: Hair Coat Development and Hair Cyclementioning
confidence: 99%
“…Hair follicle development is a complex morphogenetic process and undergoes periodic stages of growth (anagen), regression (catagen), and relative quiescence (telogen) [ 10 12 ]. The process of hair follicle formation and differentiation relies on many regulating molecules including messenger RNAs (mRNAs) and micro RNAs (miRNAs) [ 13 15 ], as well as a variety of signalling systems, such as the Wnt, Notch, bone morphogenetic protein (BMP), and fibroblast growth factor (FGF) pathways [ 16 21 ]. LncRNAs are RNA transcripts longer than 200 nucleotides that lack open reading frames (ORF) and protein-coding capabilities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%